2021
DOI: 10.1007/s10879-021-09499-3
|View full text |Cite|
|
Sign up to set email alerts
|

Training Public Sector Clinicians in Competency-Based Clinical Supervision: Methods, Curriculum, and Lessons Learned

Abstract: This article describes an initiative to train public sector clinicians in competency-based clinical supervision. It was delivered as an 18-session course taught online to clinicians employed in departments of behavioral health in nine Southern California counties. The curriculum was co-constructed by a team of clinical supervision scholars and leaders who then served as instructors. Each two-hour meeting addressed a specific topic for which a training video had been prepared, usually featuring a member of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Several authors have already identified the promising potential of DP for psychodynamic supervision (e.g., Hilsenroth & Diener, 2017; Miller et al, 2008; Rousmaniere et al, 2017; Tracey et al, 2014), proving the time psychotherapists spend engaged in DP significantly predicts better treatment outcomes (Chow et al, 2015). Nevertheless, despite longstanding efforts to implement DP and other competency-based models in clinical settings, researchers continuously point to the fact that it has yet to become a standard practice in the real world (e.g., Falender & Shafranske, 2017; Hutman et al, 2021). Thus, many are calling for feasible DP frameworks judiciously tailored for real-life clinical supervision (Clements-Hickman & Reese, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have already identified the promising potential of DP for psychodynamic supervision (e.g., Hilsenroth & Diener, 2017; Miller et al, 2008; Rousmaniere et al, 2017; Tracey et al, 2014), proving the time psychotherapists spend engaged in DP significantly predicts better treatment outcomes (Chow et al, 2015). Nevertheless, despite longstanding efforts to implement DP and other competency-based models in clinical settings, researchers continuously point to the fact that it has yet to become a standard practice in the real world (e.g., Falender & Shafranske, 2017; Hutman et al, 2021). Thus, many are calling for feasible DP frameworks judiciously tailored for real-life clinical supervision (Clements-Hickman & Reese, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, some challenges are inherently shared by all public psychotherapeutic services around the world, which could be broadly summarized as follows:Public psychotherapy must adhere to the principles of distributive justice (i.e., overarching equality of access to scarce health resources; Daniels, 2001), including, for example, the issue of patient prioritization and maintaining cost-effectiveness. Thus, supervision in publicly funded settings carries the dual task of serving not only the needs of the supervisee and the therapeutic dyad, but also the broader organizational interests of the health care system (Carroll & Rounsaville, 2007; Hutman et al, 2021). In other words, it serves a gatekeeping function by supporting decision-making processes such as rationing care (Walton & Grenyer, 2002), responsible not only for those who get treated, but also for those who do not.…”
Section: The Matrixmentioning
confidence: 99%
“…While progress has been made in developing competency-based supervision to support clinicians in delivering specific evidence-based treatments targeting measurable outcomes (e.g., Danzi et al, 2020; Dorsey et al, 2017; Hutman et al, 2021), none of this work really addresses the complex needs of supervision for clinical work with patients diagnosed with psychosis described above. Concrete strategies for measuring supervisory competencies and improving fidelity to these treatment models offer little to clinicians struggling to form relationships with patients for whom connection may be threatening or overwhelming.…”
mentioning
confidence: 99%